KOMPARASI KUALITAS LAYANAN APLIKASI MOBILE PEMESANAN TIKET KERETA SAAT MUDIK 2025 MENGGUNAKAN WEBQUAL 4.0 DAN ULASAN PENGGUNA - Falgenti, Kursehi; Nur Fadhilah, Qisty (Program Studi Informatika Fakultas Teknik Universitas Janabadra, 2025)
The high interest of the public in traveling home for the Eid holiday has led to surge in online train ticket bookings, particularly through applications such as KAI Access, Traveloka, and Tiket.com. During this period, ticket booking applications experience heavy service loads, making it an ideal moment to evaluate the optimal service quality of each application under high-demand conditions. This study aims to analyze the service quality of three applications using the WebQual 4.0 model, which includes three main dimensions: usability, information quality, and service interaction. The method applied is mixed methods, with quantitative data collected through questionnaires from 300 active users (100 per application), and qualitative data obtained from content analysis of user reviews on the Google Play Store. The results show that Tiket.com achieved the highest score in usability with an average value of 3.31, followed by Traveloka (3.26), and KAI Access (3.17). In the information quality dimension, Traveloka ranked highest with a score of 3.31, followed by Tiket.com (3.18), and KAI Access (3.09). Traveloka also led in service interaction with a score of 3.93, indicating system stability and ease of service access. Conversely, KAI Access still faces challenges in delivering up-to-date information and maintaining performance during high traffic periods. In conclusion, although all three applications fall into the “fair to good” category, improvements are still needed, particularly in terms of information delivery and system responsiveness during peak usage.